Challenges and Opportunities in Equitable Distribution of NTFP among the Usufructs of Nepal - Rawal, Rana Bahadur (Nepal Journal of Multidisciplinary Research, 2020)
Non-timber forest products (NTFPs) are plants or plant parts that have perceived economic or consumption value sufficient to encourage their collection and removal from the forest. The main objective of this study is to identify the challenges and opportunity in equitable distribution of NTFPs among the usufructs. The study was conducted among the 446 usufructs of Dolpa, Salyan and Banke of Western Nepal. The study had adopted the simple random sampling technique to select the respondent from the study areas. Mixed method approach was applied for data collection. The findings show that there were some challenges due to inadequate knowledge and incomplete information on products, markets and prices on the part of collectors/producers. 54.9 percent of them said lack of the market system of providing price of NTFPs was the key challenges/barriers for the equitable distribution of usufructs followed by dominance of middleman/traders (52.2%), lack of accessibility of big market (45.3%), lack of awareness of price of NTFPs (12.4%) and lack of accessibility to MPIS (6.2%). Though, there were more opportunities to promote the NTFP. Demand of NTFPs mainly comes for three major use categories: 1. Pharmaceutical Industry & Research, 2. Health Care, and 3. Consumer Market. The Government of Nepal should provide the technical skills through training and orientation to usufructs about the proper cultivation and harvesting of NTFP and knowledge on use of MPIS which can directly contribute in the sustainable management of NTFP.